Psalm 69:36 in the light of the Zion-tradition - Groenewald, Alphonso (Old Testament Essays, 2008)
Zion is explicitly mentioned in Psalm 69:36a. This article will endeavour to outline its significance for the interpretation of the text of Psalm 69. The text of Psalm 69 functioned as an individual lament in the pre-exilic period. In the crisis of the exilic / early post-exilic period, as well as later in the post-exilic period, it became a vehicle for a divided Jewish community to express their laments as the personified 'I'. Consequently, a new perspective has been created in this text: the sufferer of the basic text has now come to reflect the suffering community in the different epochs in the post-exilic Judah. Moreover, it is significant that the end of this text discovered the hope for Zion and the cities of Judah in God's faithfulness expressed to the suffering individual.
free